2020
DOI: 10.1001/jamanetworkopen.2020.26324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pod e-Cigarettes vs Cigarettes on Carcinogen Exposure Among African American and Latinx Smokers

Abstract: IMPORTANCE Fourth-generation nicotine salt pod system (NSPS) electronic cigarettes (e-cigarettes) are the leading class of e-cigarettes. They contain high nicotine concentrations, which may facilitate switching among smokers, but could also lead to increased exposure to nicotine and biomarkers of potential harm. African American and Latinx smokers experience significant tobaccorelated health disparities. The potential of NSPS e-cigarettes to reduce smoking-related harm among these groups is unknown. OBJECTIVET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 68 publications
(98 citation statements)
references
References 36 publications
(62 reference statements)
5
87
0
4
Order By: Relevance
“…Supporting the idea that nicotine dose is an important determinant of success in smoking cessation, quitting rates in the population as a whole are higher when later‐generation e‐cigarettes with higher power such as tank‐style devices are used compared with first‐generation devices 90 and when e‐cigarettes are used more frequently 90,91 . The only trial to date using modern pod devices was a harm reduction study using 59 mg/mL nicotine pods 92 . This study found a reduction in a primary pulmonary carcinogen exposure overall, a reduction of tobacco cigarette consumption in those who used both e‐cigarettes and continued to smoke, with approximately one‐fourth of the participants switching exclusively to e‐cigarettes 92 .…”
Section: Potential To Aid Smoking Cessation/support Harm Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supporting the idea that nicotine dose is an important determinant of success in smoking cessation, quitting rates in the population as a whole are higher when later‐generation e‐cigarettes with higher power such as tank‐style devices are used compared with first‐generation devices 90 and when e‐cigarettes are used more frequently 90,91 . The only trial to date using modern pod devices was a harm reduction study using 59 mg/mL nicotine pods 92 . This study found a reduction in a primary pulmonary carcinogen exposure overall, a reduction of tobacco cigarette consumption in those who used both e‐cigarettes and continued to smoke, with approximately one‐fourth of the participants switching exclusively to e‐cigarettes 92 .…”
Section: Potential To Aid Smoking Cessation/support Harm Reductionmentioning
confidence: 99%
“…The only trial to date using modern pod devices was a harm reduction study using 59 mg/mL nicotine pods 92 . This study found a reduction in a primary pulmonary carcinogen exposure overall, a reduction of tobacco cigarette consumption in those who used both e‐cigarettes and continued to smoke, with approximately one‐fourth of the participants switching exclusively to e‐cigarettes 92 . Another recent study reported higher quit rates with a combination of nicotine patches and nicotine‐containing e‐cigarettes compared with the patches and nicotine‐free e‐cigarettes, 81 which supports the importance of adequate nicotine substitution as well as the potential of e‐cigarettes to be used as an aid in addition to the currently licensed pharmacotherapies.…”
Section: Potential To Aid Smoking Cessation/support Harm Reductionmentioning
confidence: 99%
“…This is a secondary analysis from the first reported randomized clinical trial of NSPS ECs testing effects on toxicant exposure among AA and Lx adults who smoke [ 19 ]. As described in detail elsewhere [ 19 ], this multi-site study was conducted from July 2018 to May 2019.…”
Section: Methodsmentioning
confidence: 99%
“…After being introduced to the U.S. market in 2007, e-cigarettes quickly gained popularity. While the long-term health effects of e-cigarettes await more research, existing evidence suggests that e-cigarettes may exude fewer toxins compared to combustible cigarettes [ 1 , 2 , 3 , 4 , 5 ]. As a result, there has been more discussion in recent years about encouraging a complete switch to e-cigarettes among smokers who otherwise are unable or unwilling to quit smoking [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%